Índice de governança corporativa: criação de valor e desempenho nas cooperativas de crédito - Jose Roberto de Souza Francisco (2014)
In this research, it was intended to analyze the relation between good practices of corporative governance and the relation with value/performance creation, of Financial Cooperatives along the period of 2010 and 2012. The aim of the research was to create and to validate a rate of corporative governance for Financial Cooperatives, for then analyzing the relation between good practices of governance and the value/performance creation, having as question problem: Do good practices of corporative governance provide value creation for Financial Cooperatives? The theoretical boarding was based on corporative governance, value creation and financial cooperatives. Initially the questionnaire was collected (survey research) being based on the aspects of corporative governance. Meanwhile, data of patrimonial balance sheets of the years of 2010 and 2012 of financial cooperatives were collected, in order to support the variables value and performance creation. After, then, the data were compiled so that the statistical/econometric procedures could be initiated. Due to the great number of variable, the quantitative data were grouped by means of the econometric statistical technique of factorial analysis, while the qualitative data, corporative governance, it were made by means of the econometric statistical technique of principal component analysis. The used variable of control were chosen on the basis of the literature searched along the study, and it is stood out, concerning the evaluation of value creation, that were used performance variables, and as for the performance evaluation, were used value creation variables. Thus, the research was initiated by means of the creation of ratings from factorial analysis for the identification of dependent latent variables related to value and performance creation; after that, the creation of rates from the principle components analysis for the creation of independent latent variables related to corporative governance; Finally, it was verified, from panel data regression models, the influence of variables and rates related to corporative governance with the rates of value and performance creation. On the basis of the research, it was stayed the evidence that the Corporative Governance Rate (CGR) is mainly impacted by the Executive Management, representing 40,31% of the CGR importance, followed by the dimension Representation and Participation, with 34/07% of the CGR importance. Inside the Executive Management, it can be highlighted the technique qualification of managers representing more than a halt of importance of the dimension Executive Management, while for the dimension Representation and Participation, more than a half of its importance come from cooperativist education of employees and associates. Analyzing the variables, the research has pointed to the following Constructs: Construct Value Creation having generated the latent variable Value Aggregation, object of factorial analyses formed by the variable Inv.Tot. Total Investment; EVA Economic Value Aggregation; Inv.A.Fixo Fixed Asset Investment; CDG Working Capital Investment; Construct Value Creation having generated the latent variable To develop Value, object of factorial analyses formed by means of the variables AVA Aggregation Value Annalise; EBITDA/AT - LAJIRDA/Total Asset; Marg.L.Op Operating profit margin; and Rent.KP. Return on Equity; and, finally, the Construct Performance having generated the latent variable CDG Operational, object of the factorial analyses formed by means of the variable At.Operac/CDG Resources used in Operational activity. The contribution of the work for the academy was the creation of Corporative Governance Rate (CGR) applicable to financial cooperatives. Regarding the contribution for the financial cooperatives systems, it was highlighted the finding of effectiveness of financing-economic and patrimonial management mechanisms adopted by BACEN, Financial Cooperatives head offices and OCEMG.